STUDI PEMBENTUKAN KABUPATEN LAMANDAU DI KALIMANTAN TENGAH - Dini Yunita Sari; Suwanto Adhi; Sulistyowati . (Journal of Politic and Government Studies, 2015)
Expansion of the area is the community's aspirations for progress of the region itself and how the new autonomous regions have their own authority to take care of that government control range can accelerate the process of development in the expanded area, automatically splitting is solely for the welfare of society.Conditions of public services in the area of new regional expansion remains to be improved continuously, the figure of local leaders who have the duty to lead and provide services should be the one person who has the education, as well as specific to the skills and knowledge. Expansion in one area must always be accompanied by the readiness of all components, such as society, human resources, facilities and infrastructure.This study aims to determine the cause of desire formation Lamandau District in Central Kalimantan as well as constraints and supporting the process of formation Lamandau District. In this study can be described that the process of formation Lamandau District notion derived from bureaucratic requirements and needs of the community. The legal basis used is the study of Regulation No. 129 of the 200 who now has been revised to Regulation No. 78 of 2007 on Procedures for the Establishment, Abolition and Region Merging the basis of the formation of local or regional expansion which aims to improve public services in order to accelerate the realization of public welfare . In this study is a qualitative study using a descriptive analysis of the data analysis.Suggestions that can convey the author is local government in conducting a program of formation of a new district policy, first need to prepare carefully about aspects relating to the establishment of the district such as the preparation in the areas of administration and facility infrastructures that support the creation of new districts.